PERCEPTION AND ACCEPTANCE OF THE CUSTOMERS TOWARDS HALAL PRODUCTS - Yajid, Mohd Shukri Ab; Yusuf, Eddy (International Journal of Psychosocial Rehabilitation, 2020)
Islam has introduced the concepts of halal which includes hygiene, procedures, preparation, slaughtering, display and sanitation. Today, halal has become a vital concern among the customers, especially Muslim communities as well as non-Muslim communities. There are certain elements that influence towards the purchase intentions. This study explored the factors namely; attitude, subjective norm are the variables that duly influence the purchase intention. The data has been taken from various aspects while putting questionnaire to the different dimension, where to analyze the influence regression analysis has been performed while on the other hand relationship is also ascertained, for this correlation method has been adopted to enumerate the results. The study mentioned some significant relationship among the elected variables while some extent of influencing measures has been ascertained.